Study of Two Hemp Concrete Walls in Real Weather Conditions. (November 2015) - Bejat, Timea; Piot, Amandine; Jay, Arnaud; Bessette, Laetita
Abstract: The use of bio-based materials in construction is significantly improving. One of the bio-based materials is hemp concrete which is a composite obtained by mixing a binder and the non-fibrous part of hemp, called shiv. This specific hemp concrete developed by Vicat is made with Prompt Natural Cement (PNC) as binder. In situ hygro-thermal performance assessment of this material was performed in this paper. For this both simulation and experimental measurements are conducted in parallel. In the experimental study two PASSYS test facilities are used. They are parallelepiped test cells around 30 m3 volume each. One test wall is built with the interesting façade while the five other walls are highly insulated and are non-tested walls. Test walls are subject to weather solicitations outside and hydrothermal regulation inside. The two test cells are next to each other, and the hempcrete wall is south oriented. The only difference between cells is the external coating in order to analyze the coating effect on moisture transfer: one cell is supplied with traditional hemp lime render and the other one with cement based render. In parallel, 2D numerical simulation of hygrothermal behavior of the wall was carried out using a coupled heat and moisture transport model with boundary condition from the monitored data (outside weather conditions and inside regulation). Results show a good agreement between measured and simulated data.